Analisis Gender Pencapaian Jabatan Strategik Anggota Dewan Perempuan (DPRD Mamuju Tengah) - Rara Novrayanti Salman (Tasharruf: Journal Economics and Business of Islam, 2019)
Women in the legislature have a minimum amount of let alone the position of strategic positions as the chairman is still very low so gender equality in the legislature is difficult to realize.This study aims to identify and analyze the motivations, mechanisms and barriers in strategic appointments of female council members. The research method is qualitative research. Data was collected through in-depth interviews, observations and documentation. Data was analyzed using gender theories and model analysis developed by Milles and Huberman, the data obtained then processed through three lines of qualitative data analysis namely: data reduction, data presentation and conclusions. The results show that the intrinsic motivation of female parliamentarians is highly motivated to be a leader in structure, the family also supports. Extrinsic motivation is made up of parties and factions but some male parliamentarians do not support women as chairman. The mechanism of the proposed chairman is proposed based on the decision of the faction. Structural barriers are low levels of education or human resources, lack of female self-confidence and specially acquired information about women, a small number of female parliamentarians, lack of support from male parliamentarians and electoral systems based on factional decisions, cultural barriers are the patriarchal culture that some male parliamentarians and the effect of the women's double workload after marriage.Perempuan dalam legislatif memiliki jumlah yang minim apalagi pencapaian jabatan strategis sebagai ketua masih sangat rendah sehingga kesetaraan gender dalam legislatif sulit diwujudkan. Penelitian ini bertujuan untuk mengetahui dan menganalisis motivasi, mekanisme, dan hambatan dalam pencapaian jabatan strategis anggota dewan perempuan. Metode penelitian adalah penelitian kualitatif. Pengumpulan data dilakukan melalui wawancara, observasi dan dokumentasi. Data dianalisis dengan menggunakan teori-teori gender dan analisis model interaksi yang dikembangkan oleh Milles dan Huberman, data yang telah didapat kemudian diolah melalui tiga jalur analisis data kualitatif yaitu: reduksi data, penyajian data dan penarikan kesimpulan.Hasil penelitian menunjukkan motivasi instrinsik anggota dewan perempuan sebagian besar memiliki motivasi menjadi ketua dalam alat kelengkapan, dukungan keluarga juga diperoleh.Motivasi ekstrinsik diperoleh dari partai dan fraksi tetapi sebagian anggota dewan laki-laki tidak mendukung perempuan dalam mencapai jabatan sebagai ketua. Mekanisme Pengusulan calon ketua diusulkan atas keputusan fraksi. Hambatan structural yaitu rendahnya tingkat pendidikan atau sumber daya manusia, kurangnya rasa pecaya diri perempuan yang diikuti dengan kurangnya informasi yang diperoleh terkhusus mengenai perempuan, minimnya jumlah anggota dewan perempuan, kurangnya dukungan anggota dewan laki-laki dan sistem pemilihan ketua yang melibatkan fraksi, hambatan kultural yaitu budaya partiarki yang dianut sebagian anggota dewan laki-laki dan pengaruh beban kerja ganda perempuan karena telah menikah.